2009
DOI: 10.1002/hyp.7465
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic model calibration using discontinuous data: an example from the upper Blue Nile River Basin of Ethiopia

Abstract: Abstract:Hydrologic models using water balance approaches typically use continuously observed streamflow data for calibration. Many large river basins in developing countries such as the upper Blue Nile River Basin of Ethiopia have discontinuous hydrographs that contain short continuous periods. Therefore, the efficient use of observed hydrographs for calibration of a hydrologic model is important to improve model performance. The goal of this study is to assess how limitations of continuity and duration in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…If there are calibrations using 6-month data that could achieve performances similar to the benchmark calibration, stage two of the experiment was initialized, in which the subsets of 6-month data records were used for calibration to explore the performance of a calibration period shorter than six months. Kim and Kaluarachchi (2009) and Yapo et al (1996) showed that data from high-flow periods are more informative than data from low-flow periods for model calibration. As our study explored the possibility of the highest performance of certain lengths of records for calibration, the 3-month, 1-month data and 1-week datasets with highest average streamflow in the 6-month records were employed as the representatives to calibrate the model and conduct the evaluation at these three temporal scales.…”
Section: Experiments Designmentioning
confidence: 99%
See 2 more Smart Citations
“…If there are calibrations using 6-month data that could achieve performances similar to the benchmark calibration, stage two of the experiment was initialized, in which the subsets of 6-month data records were used for calibration to explore the performance of a calibration period shorter than six months. Kim and Kaluarachchi (2009) and Yapo et al (1996) showed that data from high-flow periods are more informative than data from low-flow periods for model calibration. As our study explored the possibility of the highest performance of certain lengths of records for calibration, the 3-month, 1-month data and 1-week datasets with highest average streamflow in the 6-month records were employed as the representatives to calibrate the model and conduct the evaluation at these three temporal scales.…”
Section: Experiments Designmentioning
confidence: 99%
“…Generally in the two dry basins, if the model performance in the calibration period is good, 6-month data from wet years or wet periods make more reliable simulations in the validation period than the ones from dry years or dry periods. Kim and Kaluarachchi (2009) demonstrated that data from high-flow periods have greater control on model calibration because they are more informative with regard to parameter identification. In this context, our suggestion is in line with those made by Yapo et al (1996) and Melsen et al (2014): data from wetter periods are preferred for model calibration.…”
Section: Implications For Future Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2008a,b; Setegn et al, 2009a,b; Abtew et al. , 2009; Kim and Kaluarachchi, 2009). In this study, the physically based SWAT model was applied to Anjeni‐gauged watershed for prediction of soil erosion and sediment yield.…”
Section: Introductionmentioning
confidence: 96%
“…The Nash-Sutcliffe efficiency index, the final value reported as a result of the Nash-Sutcliffe Model efficiency test (Nash and Sutcliffe 1970), is a widely used statistic for this purpose (Oudin et al 2006;Bardossy and Das 2008;Kim and Kaluarachchi 2009;van der Heijden and Haberlandt 2010).…”
Section: Introductionmentioning
confidence: 99%